Cigarette taxation and consumption in The Czech Republic: Have these factors influenced tax revenue? - Michal Krajňák (Financial Internet Quarterly, 2024)
The article evaluates the development of the tax burden on cigarettes in the Czech Republic from 1993 to the end of 2023. Tax burden is represented by effective tax rate. The research results show that the tax burden on these products is still increasing. Not only does the tax burden increase, but so does the price of these products. The regression analysis results show that quantities such as the price of cigarettes, the effective tax rate or the amount of cigarettes consumed are factories that positively influence tax revenue. Since the tax rate or the price of these products constantly increases, the tax revenue is also increasing. It increased almost six- fold over the entire analyzed period. At the same time, it was found that other factors, such as the average wage, also affect the tax revenue. It is necessary to consider that the cigarette consumption has been showing a downward trend in recent years. However, the reason is not only the increasing tax burden and the price of these products but also the transition of consumers to so-called e-cigarettes. A reduction in cigarette consumption may be reflected in the future by reducing healthcare costs, which will create potential reductions in public health insurance payments.
Keywords: C50; H20; I10; 330; Cigarette; Cigarette Taxation; Cigarette Consumption; Laffer Curve; Tax Rate